HIV Incidence and Associated Risk Factors Among Young Men Who Have Sex With Men in Tianjin, China: Retrospective Cohort Study - Yan Guo; Hui Gong; Xiangyu Yan; Xinying Zhang; Tielin Ning; Zhongquan Liu; Long Li; Jie Yang; Liu Li; Changxu Ma; Zhuang Cui; Maohe Yu (JMIR Public Health and Surveillance)
Abstract BackgroundYoung men who have sex with men (YMSM) have a higher risk of HIV infection. However, evidence of HIV incidence from large cohort studies is limited in this key population, particularly among Chinese YMSM. ObjectiveThis study aimed to investigate the HIV incidence and associated risk factors among YMSM aged 16‐24 years in Tianjin, China. MethodsWe conducted a retrospective cohort study among men who have sex with men aged 16‐24 years from October 2017 to December 2022 through the largest local nongovernmental organization serving men who have sex with men in Tianjin. Participants who responded to the investigations at least twice during the study period were included. They completed questionnaires on demographic information, sexual behaviors, psychoactive substance use, and sexually transmitted infection status. Simultaneously, their blood samples were collected for HIV testing. HIV incidence was calculated by dividing the sum of observed HIV seroconversions by the observed person-years (PYs). A Cox proportional hazards regression model was used to identify risk factors associated with HIV incidence. ResultsA total of 1367 HIV-negative YMSM were included in the cohort, among whom 62 seroconversions occurred, contributing 2384.2 observed PYs; the total incidence was 2.6 (95% CI 2.0‐3.2) per 100 PYs. The segmented HIV incidence rates were 3 (95% CI 1.5‐4.5), 2.4 (95% CI 1.5‐3.3), and 2.7 (95% CI 1.5‐3.9) per 100 PYs for 2017‐2018, 2019‐2020, and 2021‐2022, respectively. Compared to YMSM who had been followed up fewer than three times, those followed up three or more times had a relatively lower risk of HIV infection (Adjusted hazard ratio [AHR] 0.553, 95% CI 0.325‐0.941). YMSM who preferred finding sexual partners offline had a higher risk of HIV infection compared to those who preferred finding sexual partners online (AHR 2.207, 95% CI 1.198‐4.066). Compared to YMSM without syphilis, those infected with syphilis had an increased risk of HIV infection (AHR 2.234, 95% CI 1.137‐4.391). Additionally, YMSM who used psychoactive substances had a higher risk of HIV infection compared to those who did not use such substances (AHR 2.467, 95% CI 1.408‐4.321). ConclusionsOur study complements data on HIV incidence among YMSM in large cities across China. Syphilis infection and the use of psychoactive substances were risk factors associated with HIV occurrence, demonstrating an urgent need for tailored prevention and control interventions for this key population.